Methods of Training Future Border Guard Officers Shooting with Simulation of Combat Psychological Factors - Zabolotnyi, Serhii; Olytskyi, Oleksandr (Educological discourse, 2023)
The article presents the methodology of training future border guard officers shooting using techniques of combat psychological factors simulation, that was successfully used for practical training of future border guard officers at the National Academy of the State Border Guard Service of Ukraine. The Firearms Training Department of the Academy has started to organize shooting training sessions with the psychological combat factor simulation as part of the professional training of border guards, focusing on the psychological, physical and tactical skills of future border guards, enabling them to realize the importance of firearms training as a part of a military unit. The use of combat psychological factors simulation during practicing combat shooting has proved effective to simulate a combat situation and effect of enemy fire. The shooting training of the mechanized platoon personnel, according to a proposed method, has been organized in three sections, between sections - synchronously, and within the section - sequentially, which allowed each cadet to work out a tactical task as the commander of a section of a mechanized platoon. When conducting practical classes according to the methods and techniques proposed, the instructors applied a single method of preparation and conducting fire training at training sites. The experience gained by the cadets during practical training in the discipline "Firearms training" showed that such training increases the level of the border guard officers’ skills to solve combat shooting tasks with small arms, improving their individual skills, as well as their readiness to perform shooting tasks in conditions of modern combat, and also stimulate the cognitive activity of future border guards. Thus, continuous training of instructors, full methodological, material and technical support and proper organization and high-quality conduct of practical classes, using simulations of combat psychological factors, maximizes the level of acquired knowledge and skills of future border guard officers.